Predicting concordance with multilayer compression bandaging - Miller, C.; Kapp, S.; Newall, Nelly; Lewin, Gill; Karimi, L.; Carville, Keryln; Santamaria, Nick (MA Healthcare Ltd, 2011)
Objective: To examine the relationship between concordance with multilayer compression bandaging and a number of client and wound characteristics, including wound severity, health status and client independence with respect to activities of daily living. Method: Using data gathered for a randomised controlled trial that compared two types of antimicrobial dressings on infected or critically colonised lower leg ulcers, we explored the level ofconcordance with compression therapy by patients with wounds that had an ankle brachial pressure index of between 0.8 and 1.2. Results: A logistic regression analysis found that increased pain and wound size, older age and shallow wound depth were all significant predictors of non-concordance with multilayer compression bandaging. Conclusion: Although the results suggest that pain, wound size, age and wound depth are all significant predictors of non-concordance with multilayer bandaging, the generalisability of these results is limited, given that data were gathered in the context of a RCT. Further studies are required to explore the relative contribution of predictors of concordance with compression therapy, in order to help inform strategies that promote it and, thereby, optimise healing. Conflict of interest: None.